The impact of descriptive and injunctive norms on engagement in mobile phone use while driving in young drivers: A systematic review. (September 2022) - Nicolls, Michelle; Truelove, Verity; Stefanidis, Kayla B
Highlights: Young drivers believe their peers frequently engage in phone use while driving. Young drivers believe their peers disapprove of distracted driving. Higher perceived peer engagement correlated with increasing phone use while driving. Higher perceived approval correlated with increasing distracted driving. Abstract: Background/objectives : Prior research indicates that younger adults overestimate their peers' engagement in risk-taking behaviours, with these estimates being directly associated with engagement in such behaviours. However, the extent to which younger adults perceive their peers' approval of, and engagement in, road traffic violations (such as mobile phone use while driving) is yet to be clearly identified. Further, the influence of such perceptions on subsequent mobile phone use while driving behaviours remains unclear. Accordingly, the aim of this systematic review was to (a) examine young drivers' perceptions regarding their peers' approval of (injunctive norms), and engagement in (descriptive norms) mobile phone use while driving and (b) to identify whether such perceptions increase young drivers own engagement in the behaviour. Methods : Studies were eligible for review if they measured (a) perceived social norms (descriptive/injunctive) and (b) the relationship between such norms and mobile phone use while driving in younger adults aged 16–25 years. Searches were conducted in December 2021, using Pubmed, Scopus, Web of Science, and TRID. Five articles were included in the review. Results : Overall, the results indicate that young drivers perceive their peers to engage in mobile phone use while driving on a frequent basis, however they typically believe that their peers disapprove of the behaviour. The majority of studies indicated that descriptive norms were significantly associated with increasing engagement in mobile phone use while driving (including distracted driving behaviours). Finally, the few studies that investigated injunctive norms on mobile phone use while driving indicated positive correlations between perceived peer approval and increasing distracted driving behaviour. Discussion : The findings highlight the importance of social norms in influencing behaviour, indicating that both descriptive and injunctive norms warrant further investigation when examining the impact of peer influences on mobile phone use while driving.